Spatial and temporal changes of outdoor thermal stress: influence of urban land cover types - Mohammad A. Rahman; Eleonora Franceschi; Nayanesh Pattnaik; Astrid Moser-Reischl; Christian Hartmann; Heiko Paeth; Hans Pretzsch; Thomas Rötzer; Stephan Pauleit (Scientific Reports, 2022)
Abstract Green infrastructure (GI) has emerged as a feasible strategy for promoting adaptive capacities of cities to climate change by alleviating urban heat island (UHI) and thus heat stress for humans. However, GI can also intensify the winter cold stress. To understand the extent of UHI within a city as well as the link between outdoor thermal stress both diurnally and seasonally, we carried out an empirical study in Würzburg, Germany from 2018 to 2020. At sub-urban sites, relative humidity and wind speed (WS) was considerably higher and air temperature (AT) lower compared to the inner city sites. Mean AT of inner city sites were higher by 1.3 °C during summer and 5 °C during winter compared to sub-urban sites. The magnitude followed the spatial land use patterns, in particular the amount of buildings. Consequently, out of 97 hot days (AT > 30 °C) in 3 years, 9 days above the extreme threshold of wet bulb globe temperature of 35 °C were recorded at a centre location compared to none at a sub-urban site. Extreme heat stress could be halved with 30–40% cover of greenspaces including grass lawns, green roofs, and green walls with little compromise in increasing winter cold stress.